Perancangan E-Booklet Sebagai Media Informasi Sentra IKM Kreatif Semanggi Harmoni Surakarta - Adrian Mahatma; Martin Setyawan (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Sentra IKM Kreatif Semanggi Harmoni is a facility of the Surakarta City Cooperative and Industrial Service dedicated to supporting the growth and development of small and medium industries (IKM) in Surakarta City. This center already provides adequate facilities for the general public, but due to a lack of information dissemination, this center is not well known by the community, especially in Surakarta City. Through mixed methods research applying a linear strategy, this study combines quantitative and qualitative approaches to design an effective e-booklet as an information medium. Qualitative data was obtained through interviews with the Center's managers, IKM members, and design experts. The research results show that the designed e-booklet is able to present comprehensive information about the Sentra IKM Kreatif Semanggi Harmoni, starting from the Center's profile, facilities, to the profiles of IKM members and their superior products. The attractive e-booklet design also successfully attracted the interest of the target audience. Thus, this e-booklet is expected to be an effective information medium to increase the visibility of the Sentra IKM Kreatif Semanggi Harmoni in the eyes of the public, especially in Surakarta City.